Elevated relative humidity significantly decreases cannabinoid concentrations while delaying flowering development in Cannabis sativa L. - Corredor-Perilla, Ingrid Carolina; Kwon, Tae-Hyung; Park, Sang-Hyuck (Frontiers in Plant Science, 2025)
IntroductionRelative humidity (RH) is critical for regulating transpiration, plant morphology, and the biosynthesis of secondary metabolites in crops. However, its specific impacts on cannabis (Cannabis sativa L.) genotypes, especially concerning optimal growth and cannabinoid concentration, remain inadequately understood.This study aimed to investigate the effects of canopy-level RH on plant development and cannabinoid concentration in a CBD–dominant strain.MethodsPlants were cultivated under controlled conditions at two distinct RH ranges: low RH (37-58%) and high RH (78-98%). Growth metrics, including stem length, trunk diameter, number of nodes, apical internode spacing, and flowering time, were recorded weekly. Upon floral maturation and harvest, biomass and cannabinoid concentrations were measured. A total of 14 cannabinoids were quantified via high-performance liquid chromatography (HPLC) to assess compositional shifts under different RH conditions.ResultsCultivation under high RH resulted in a reduced vapor pressure deficit (VPD) ranging from 0.62 kPa to 0.25 kPa during flowering, indicating values outside the optimal range for cannabis cultivation. This environment led to significant reductions in total biomass (-75.3%), flower biomass (-71.0%), trunk diameter (-0.4%), and node count (29.3%), compared to low RH conditions (n = 10 per range, p < 0.001). Conversely, stem length increased by 9.7%, and apical internodal spacing expanded by 0.04% under high RH (n = 10, p < 0.0001). Flowering was delayed by three weeks with high RH, accompanied by notable reductions in both vegetative growth and inflorescence production. Furthermore, high RH significantly suppressed cannabinoid accumulation: cannabidiolic acid (CBD-A), cannabidiol (CBD), and cannabichromenic acid (CBC-A) levels decreased by approximately 4.9-fold, 3.2-fold, and 13-fold, respectively. Total cannabinoid concentrations of CBD and CBC were similarly diminished by 4.6-fold and 1.5-fold (n = 10, p < 0.0001).DiscussionThis study highlights that elevated canopy-level humidity, outside optimal VPD thresholds, can significantly delay flowering, reduce biomass accumulation, and negatively impact cannabinoid concentrations in Cannabis sativa L. cv. Cherry Berry.